Teaching Foreign Languages through Digital Platforms: Advantages and Disadvantages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study delves into how effective digital platforms are when it comes to teaching foreign languages, zeroing in on what they do well and where they fall short. We looked at popular tools like Duolingo, Babbel, and Coursera, gathering insights from user surveys and digging into their content firsthand. What stood out as the big wins were accessibility—learners can jump in anytime, anywhere—along with interactive features that keep things engaging and a cost-effectiveness that makes these platforms a steal compared to traditional classes[1]. On the flip side, there were some real drawbacks: the lack of personalized feedback left users wanting more tailored guidance, and the skimpy attention to speaking skills meant fluency in real conversations often lagged[2]. The takeaway? These digital tools can definitely play a supporting role alongside old-school methods, but they’ve got some gaps to fill if they’re going to stand on their own. Our findings suggest there’s potential here, but it’ll take some tweaking to iron out the kinks.